EVALUASI TATA KELOLA PASAR MENUJU PASAR YANG ADIL, EFISIEN, DAN BERKELANJUTAN: Evaluasi kebijakaan, Tata Kelola Pasar, PasarTradisional, Kota Kupang - 26, sulman; Indriyati; Yohanes Kornelis Ethelbert; Kristianus Simon H.Molan (Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the management of Oeba Market in Kupang City using the public policy evaluation approach according to William N. Dunn's theory. Pasar Oeba is one of the main traditional markets in eastern Indonesia that faces various managerial problems, ranging from low trader participation, weak hygiene management, to ineffective regulations. Unlike previous studies that only highlighted technical, procedural, or SWOT-based aspects, this study offers a more comprehensive analysis using Dunn's six evaluation criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research method used is descriptive qualitative with data collection techniques through observation, Deph Interview, documentation, and literature study. The results show that the management of Oeba Market in Kupang City has not fully met the principles of ideal policy evaluation, especially in terms of participation and management efficiency. This study provides strategic recommendations to strengthen market governance through policies that are more participatory, transparent, and based on local needs.